Assessment of functioning and disability in patients with low back pain – the low back pain assessment tool. Part 1: development. Issue 17 (14th August 2022) - Ibsen, Charlotte; Schiøttz-Christensen, Berit; Vinther Nielsen, Claus; Hørder, Mogens; Schmidt, Anne Mette; Maribo, Thomas
Abstract: Purpose: To present the process used to develop the low back pain (LBP) assessment tool including evaluation of the initial content validity of the tool. Methods: The development process comprised the elements: definition of construct and content, literature search, item generation, needs assessment, piloting, adaptations, design, and technical production. The LBP assessment tool was developed to assess the construct "functioning and disability" as defined by the International Classification of Functioning, Disability and Health (ICF). Involvement of patients and health professionals was essential. Results: The elements were collapsed into five steps. In total, 18 patients and 12 health professionals contributed to the content and the design of the tool. The LBP assessment tool covered all ICF components shared among 63 ICF categories. Conclusions: This study presents the process used to develop the LBP assessment tool, which is the first tool to address all ICF components and integrate biopsychosocial perspectives provided by patients and health professionals in the same tool. Initial evaluation of content validity showed adequate reflection of the construct "functioning and disability". Further work on the way will evaluate comprehensiveness, acceptability, and degree of implementation of the LBP assessment tool to strengthen its use for clinical practice. Implications for Rehabilitation: A biopsychosocial and patients-centred approach is a strong foundation for identifying the many relevant aspects related to low back pain (LBP). Responding to a lack of tools to support a biopsychosocial and patients-centred approach the LBP assessment tool was developed using a robust, multi-step process with involvement of patients and health professionals. The LBP assessment tool is a strong candidate for a user-friendly tool to facilitate use of the International Classification of Functioning, Disability and Health in routine clinical practice.